Presentation - Dossier "Religion and Health" - Vol. 14, No. 41, Jan./Mar. 2016 - Antonio Geraldo Cantarela (Horizonte, 2016)
Presentation: Dossier "Religion and Health" - Vol. 14, No. 41, Jan./Mar. 2016